Do small caps generate above average returns in the Brazilian stock market? - Matheus José Silva de Souza; Danilo Guimar\~aes Franco Ramos; Marina Garcia Pena; Vinicius Amorim Sobreiro; Herbert Kimura (Review of Development Finance, 2018)
Some studies suggest that low capitalization stocks have great potential to provide returns above the market average, although some indicate that investment in small caps should be avoided, since they are market anomalies with low liquidity. This article develops a method based on an automated trading system (ATS) applied to the Brazilian stock market, and investigates the relevance of small caps to the investor. The study indicates that, in the case of the Brazilian stock exchange, although there is a possibility of high returns the profitability of technical analysis of small caps is similar to strategies using blue chips.
Keywords: G11; G15; G17; 650; Small caps; Technical analysis; Brazilian stock market; Moving averages